Multi-modal 3D Simulation Makes the Impossible Possible. Issue 4 (April 2018) - Ganske, Ingrid M.; Schulz, Noah; Livingston, Katie; Goobie, Susan; Meara, John G.; Proctor, Mark; Weinstock, Peter
Abstract : Summary: B.Y. was born full term after a large vertex encephalocele was diagnosed prenatally. The unique challenge to repairing B.Y.'s encephalocele was a microcephalic skull and large proportion of likely functional extracranial brain tissue, which would need to be preserved. At Boston Children's Hospital, a simulation-based collaborative presurgical planning and rehearsal process, using both digital and 3D printed models, enabled successful technical completion and outcome of an otherwise inoperable case.